Коммуникативный компонент в образовательном пространстве Крыма - Мамутова, Х.Э. (Культура народов Причерноморья, 2014)
В статье рассматривается межкультурная коммуникация в образовательном
пространстве Крыма. В образовательном процессе возникает и широко обсуждается новая система
целей и ценностей образования, восстанавливается концепция личности. Реакцией на возникновение
новых социокультурных реалий со стороны мировой науки стала разработка соответствующих
образовательных стратегий. В практической деятельности культурологов в полиэтническом,
мультикультурном Крыму в ситуации полилингвизма, используются различные модели межкультурной
коммуникации в их разных взаимодействиях. В частности, использование диалогической модели при
решении проблем лингвакультурологии, без чего невозможно сформировать межкультурную
компетентность, необходимую в процессах общения и образования. У статті розглядається міжкультурна комунікація в освітньому просторі Криму. В
освітньому процесі виникає і широко обговорюється нова система цілей і цінностей освіти,
відновлюється концепція особистості. Реакцією на виникнення нових соціокультурних реалій з боку
світової науки стала розробка відповідних освітніх стратегій. У практичній діяльності культурологів в
поліетнічному, мультикультурном Криму в ситуації полілінгвізму, використовуються різні моделі
міжкультурної комунікації в їх різних взаємодіях. Зокрема, використання діалогічного моделі при вирішенні проблем лінгвакультурологіі, без чого неможливо сформувати міжкультурну
компетентність, необхідну в процесах спілкування та освіти. The article examines intercultural communication in the educational space of the Crimea. In the
educational process occurs widely discussed and a new system of values and goals of education, the concept of
personality is restored. In the academic and scientific revolution includes such notions: «educational space»,
«intercultural education», «multicultural learning environment», «educational technology» and others.
Response to the emergence of new social and cultural realities from the world of science has been the
development of appropriate educational strategies. In practice cultural studies in a multiethnic, multicultural
situation in Crimea multilingualism, different models of intercultural communication in their various
interactions. In particular, the use of a dialogic model, you need to solve problems lingvakulturologii, without
which it is impossible to form intercultural competence required in the processes of communication and
education. The principle of dialogue, is inextricably linked with the principle of tolerance, is not only a learning
tool, but also its purpose. The current situation in the world, associated with the phenomenon of globalization,
the development of computer technology, the Internet, require knowledge of both the mother and the languages
of other peoples, especially as his own and other cultures. Modern intellectual context determines the need of
functioning such educational projects.